Factors influencing the hepcidin response to exercise: an individual participant data meta-analysis - Fensham, N. C.; Govus, A. D.; Peeling, P.; Burke, L. M.; McKay, A. K. A. (Sports Medicine, 2023)
Background: Hepcidin, the master iron regulatory hormone, has been shown to peak 3-6 h postexercise, and is likely a major contributor to the prevalence of iron deficiency in athletes. Although multiple studies have investigated the hepcidin response to exercise, small sample sizes preclude the generalizability of current research findings. Objective: The aim of this individual participant data meta-analysis was to identify key factors influencing the hepcidin-exercise response. Methods: Following a systematic review of the literature, a one-stage meta-analysis with mixed-effects linear regression, using a stepwise approach to select the best-fit model, was employed. Results: We show that exercise is associated with a 1.5-2.5-fold increase in hepcidin concentrations, with pre-exercise hepcidin concentration accounting for ~ 44% of the variance in 3 h postexercise hepcidin concentration. Although collectively accounting for only a further ~ 3% of the variance, absolute 3 h postexercise hepcidin concentrations appear higher in males with lower cardiorespiratory fitness and higher pre-exercise ferritin levels. On the other hand, a greater magnitude of change between the pre- and 3 h postexercise hepcidin concentration was largely attributable to exercise duration (~ 44% variance) with a much smaller contribution from VO2max, pre-exercise ferritin, sex, and postexercise interleukin-6 (~ 6% combined). Although females tended to have a lower absolute 3 h postexercise hepcidin concentration [1.4 nmol·L-1, (95% CI [- 2.6, - 0.3]), p = 0.02] and 30% less change (95% CI [-54.4, - 5.1]), p = 0.02) than males, with different explanatory variables being significant between sexes, sample size discrepancies and individual study design biases preclude definitive conclusions. Conclusion: Our analysis reveals the complex interplay of characteristics of both athlete and exercise session in the hepcidin response to exercise and highlights the need for further investigation into unaccounted-for mediating factors.